Microstructure analyses of autoclaved ground dune sand-Portland cement paste - Alawad, Omer Abdalla; Alhozaimy, Abdulrahman; Jaafar, Mohd Saleh; Al-Negheimish, Abdulaziz; Abd Aziz, Farah Nora Aznieta (Elsevier, 2014)
In this study, SEM, EDX, XRD, DAT and TGA are used to perform microstructure analyses of autoclaved ground dune sand–ordinary Portland cement (GDS–OPC) pastes. Pastes containing 0%, 10%, 20%, 30% and 40% GDS as cement replacement were prepared for this purpose. The microstructure analyses were used to examine the microscale changes that occur in the GDS–OPC pastes with increasing GDS replacement levels. The SEM and EDX results showed the clear formation of dense and newly formed thin crystalline calcium silicate hydrate with a low CaO/SiO2 ratio. The XRD, DTA and TGA analyses revealed that the portlandite phase had been eliminated. The microstructure analyses reveal how GDS contributes to the strength and physical properties of concrete.